KAJIAN KRITIS TERHADAP FENOMENA FRAUD BUMN; TINJAUAN FRAUD DIAMOND THEORY - Suhartono Suhartono; Raodahtul Jannah; Namla Elfa Syariati (Islamic Economic and Business Journal, 2022)
The orientation of this research is to find out what deviation model or fraud model is carried out by the BUMN from the perspective of the Fraud Diamond Theory and how the losses caused by the fraud committed by the BUMN to the State and society. To achieve this goal, the research uses a type of qualitative research with a critical paradigm that examines a public problem or social issue in detail and depth based on a developing phenomenon using literature research methods. The results of the study show that the deviations that occur in BUMN are due to pressure from political and economic elements as well as opportunities that are the motive for committing fraud as described in the diamond fraud theory. In addition, the ability possessed makes it easier for him to do all what he thinks is right from their point of view.